Effects of education, income, and occupation on prevalence and symptoms of knee osteoarthritis - Ji Yeon Lee (Nature Portfolio, 2021)
Abstract To examine the effect of socioeconomic status (SES) as measured by three components of education level, income level, and occupation on prevalence and symptom severity of knee osteoarthritis (OA) and to determine which of these factors has the strongest association. We conducted a cross-sectional study using data from the Fifth Korean National Health and Nutrition Examination Survey that were collected between 2010 and 2012. Male and female participants 50 years or older were included. Analyses to examine the associations of the three SES components with prevalence and symptom severity of knee OA were performed. A total 9,071 participants was included in the study. As expected, lower education, lower income level, and non-managerial or no job were associated with higher prevalence of knee OA and knee symptoms. Among the three SES components, lower education was most strongly associated with knee pain and radiographic knee OA after adjusting for the other two. Lower education level is the component of SES that most strongly relates to higher prevalence of knee OA and knee symptoms. Improving societal education level might decrease the socioeconomic burden of knee OA.